Expressão gênica das interleucinas IL-4, IL-10, IL-12 e de interferon gama no baço de gatos infectados por Leishmania infantum chagasi - Vides, Juliana Peloi [UNESP] (2014)
TIn an attempt to understand the immune response of cats with visceral leishmaniasis, the present study aimed to evaluate the gene expression of interleukins IL- 4, IL-10, IL-12 and IFN-γ by real-time polymerase chain reaction in samples of spleen from cats naturally affected by the disease. For this, three groups of cats were evaluated; the first and second groups composed of six Leishmania-infected cats each, symptomatic and asymptomatic, respectively; and the third composed of six clinically healthy and uninfected cats. In symptomatic cats the mRNA expressions of IL- 4, IL -10, IL - 12 and IFN- γ were respectively supressed 2.52, 2.4, 2.3 and 0.57 times compared to the control group. In asymptomatic animals the expression of IL- 4, IL -10, IL -12 and IFN- γ were, respectively, 2.22, 2.15, 2.52 and 1.15 times lower when compared to the control group. Also, a strong correlation was observed between the expressions of IL4 and IL-10 in symptomatic cats; between IFN-γ and IL-10, IL-12 and IL-4 and between IL-12 and IL-10 in asymptomatic cats. The reducion of expression the four cytokines analyzed evidences a small involvement of Th1 and Th2 lymphocytes in the response to infection by Leishmania spp. in cats, regardless of the clinical status of animals